Coupling of a free wake vortex ring near-wake model with the Jensen and Larsen far-wake deficit models. (June 2015) - van Heemst, J W; Baldacchino, D; Mehta, D; van Bussel, G J W
Abstract: This paper presents a simple physical model to improve the currently used far-wake deficit models in the wind industry. The main improvement is deemed on the determination of the wake deficit in the near-wake. A Vortex Ring Model (VRM) is used to calculate the induced velocities in the near-wake, which are then coupled to the Jensen far-wake model and the Larsen far-wake model based on the concept of Eddy Viscosity (EV). The inviscid near-wake VRM is based on the shedding of discrete tip vortex rings released from a uniformly loaded actuator disc. The model is validated against wind tunnel measurements from experiments with a two- bladed turbine and a circular metal mesh with a uniform porosity to represent an actuator disc. The VRM shows a good agreement with the experimental data with respect to the wake deficit evolution. The VRM is coupled with two well-known engineering type far-wake models: the Jensen and Larsen wake deficit models. The results of the coupling of the VRM and the more elaborated Larsen far-wake model are compared against a 3D Large Eddy Simulation (LES) CFD model. This comparison shows the effect of different near-wake models on the development of centreline velocities in the far-wake. The centreline velocity deficit predicted by the VRM-Larsen model more closely matches LES calculations in comparison with the reference Larsen model.